ENVIRONMENTAL IMPACT AND QUALITY OF THE ENVIRONMENTAL CERTIFICATION SERVICE FOR ENERGY PROJECTS IN PERU - Espinoza Ortiz, Diego Mauricio (2021)
The nature of the present study was mainly to determine the relationship between the performance of environmental impact assessment and the quality of the environmental certification service for energy projects in the period 2016-2019. A survey was applied to the users of the environmental certification service for energy projects in the aforementioned period. The analysis and interpretation of the information was performed using correlation tests to determine the significant relationship between the dimensions of both variables. In general, the performance of the environmental impact assessment is significantly related to the quality of the environmental certification service; for the respondents, the environmental impact assessment procedures do result in environmental certifications that precisely fulfill their procedural purpose (effectiveness and tangibility relationship); likewise, the accessibility and ease of treatment during the environmental impact assessment procedures are adapted to their needs of empathy (closeness and empathy relationship). However, the respondents consider that the extent to which resources are used in the environmental impact assessment would not be rationally associated with a fast service, adequate responses and due scope (efficiency and responsiveness relationship), and that the environmental impact assessment processes would not have been executed according to the uniformity of the standard set by the governing body's regulations (consistency and reliability relationship). The impact of this research will serve as a basis in case the implementation of a quality management system for the environmental certification service is considered.